2009 International Conference on Advances in Computing, Control, and Telecommunication Technologies 2009
DOI: 10.1109/act.2009.220
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Clustering Web User Sessions Using RST

Abstract: Web usage mining has assumed importance in learning about web user's behavior and user interactions with the website. It uses data mining techniques to discover non-trivial user behavior patterns. These patterns can then be used to make the predictions of next page to be accessed by the user. Web usage mining consists of the steps like web log preprocessing, pattern discovery and pattern analysis. This paper proposes a novel approach for preprocessing wherein rough set clustering is applied to form the cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Sessionization heuristics can be broadly classified as: time-oriented (Zhou et al , 2006; Castellano et al , 2007; Peng and Zhao, 2010; Xinhua and Qiong, 2011; Dinuca and Ciobanu, 2012) and structure-oriented (Khasawneh and Chan, 2006; Fang and Huang, 2010). One approach for session identification is to use clustering techniques for grouping user sessions (Murray et al , 2006; Alam et al , 2008; Lu and Nguyen, 2009; Jyoti et al , 2009; Hussain et al , 2010; Chordia and Adhiya, 2011; Huidrom and Bagoria, 2013; Chang-bin and Li, 2010). Later, link-based sessionization heuristics were proposed as an alternate for time-oriented and structure-oriented heuristics (Bayir et al , 2009; Bayir and Toroslu, 2013; Tiknaz, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sessionization heuristics can be broadly classified as: time-oriented (Zhou et al , 2006; Castellano et al , 2007; Peng and Zhao, 2010; Xinhua and Qiong, 2011; Dinuca and Ciobanu, 2012) and structure-oriented (Khasawneh and Chan, 2006; Fang and Huang, 2010). One approach for session identification is to use clustering techniques for grouping user sessions (Murray et al , 2006; Alam et al , 2008; Lu and Nguyen, 2009; Jyoti et al , 2009; Hussain et al , 2010; Chordia and Adhiya, 2011; Huidrom and Bagoria, 2013; Chang-bin and Li, 2010). Later, link-based sessionization heuristics were proposed as an alternate for time-oriented and structure-oriented heuristics (Bayir et al , 2009; Bayir and Toroslu, 2013; Tiknaz, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the interesting user patterns, Jyoti et al (2009) presented a WUM scheme to identify individual user navigational behavior on the web. Experimental results showed that the algorithm outperforms the traditional clustering techniques in order to derive groups of users which exhibit similar access patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a test cases series that was executed for a variety of sessions, ranging from shorter ones to longer ones. For the WUM method in our trials, we employed the Markov model-based technique [25] and the association rule mining technique [26]. For the WCM technique, we used the keyword-based approach [26].…”
Section: Comparison Between Prefetching Systems Based On Wum Wcm and ...mentioning
confidence: 99%